A Comprehensive Theory of Integration. (April 2020) - Singer, Sara J.; Kerrissey, Michaela; Friedberg, Mark; Phillips, Russell
Efforts to transform health care delivery to improve care have increasingly focused on care integration. However, variation in how integration is defined has complicated efforts to design, synthesize, and compare studies of integration in health care. Evaluations of integration initiatives would be enhanced by describing them according to clear definitions of integration and specifying which empirical relationships they seek to test—whether among types of integration or between integration and outcomes of care. Drawing on previous work, we present a comprehensive theoretical model of relationships between types of integration and propose how to measure them.